2010
DOI: 10.1121/1.3377062
|View full text |Cite
|
Sign up to set email alerts
|

Transient cavitation in high-quality-factor resonators at high static pressures

Abstract: It is well known that cavitation collapse can generate intense concentrations of mechanical energy, sufficient to erode even the hardest metals and to generate light emissions visible to the naked eye [sonoluminescence (SL)]. Considerable attention has been devoted to the phenomenon of "single bubble sonoluminescence" (SBSL) in which a single stable cavitation bubble radiates light flashes each and every acoustic cycle. Most of these studies involve acoustic resonators in which the ambient pressure is near 0.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 26 publications
0
34
0
2
Order By: Relevance
“…Within the first acoustic cycle in the experiment with the water-water vapor system [121], under the experimental conditions f a = 26 kHz, Т l = 20°С, and p st = 100 atm, nucleation of a bubble, its expansion to R m ≈ 0.5 mm, its collapse, and SW in the liquid were observed. The SW amplitude measured at distance r = 1 cm from the bubble center was ~1 kbar.…”
Section: Shock Wave In Liquidmentioning
confidence: 95%
See 3 more Smart Citations
“…Within the first acoustic cycle in the experiment with the water-water vapor system [121], under the experimental conditions f a = 26 kHz, Т l = 20°С, and p st = 100 atm, nucleation of a bubble, its expansion to R m ≈ 0.5 mm, its collapse, and SW in the liquid were observed. The SW amplitude measured at distance r = 1 cm from the bubble center was ~1 kbar.…”
Section: Shock Wave In Liquidmentioning
confidence: 95%
“…In this device, bub ble oscillations only persist for several hundreds of cycles. In [121], this type of cavitation was called tran sient cavitation to distinguish it from SBSL, where the bubble lifetime is much longer.…”
Section: Shock Wave In Liquidmentioning
confidence: 98%
See 2 more Smart Citations
“…10 A system to generate acoustic cavitation at ambient pressures in excess of 30 MPa has been developed. 11 However, some studies have reported that the intensity of hydrodynamic cavitation could be increased with less energy compared with that required for acoustic cavitation. 12 In practical applications for chemical reactors, such as water treatment systems, hydrodynamic cavitation is preferable to acoustic cavitation, as it can be easily scaled up to enhance its aggressive intensity, and acoustic cavitation, moreover, has not been applied to large scale operations because of the difficulties in scaling up ultrasonic reactors.…”
Section: Introductionmentioning
confidence: 99%